1981
DOI: 10.1515/labm.1981.5.4.73
|View full text |Cite
|
Sign up to set email alerts
|

Einfluß von Alter, Geschlecht und Antikonzeptiva auf die mit Hilfe der kinetischen Nephelometrie bestimmten IgA-, IgG-, IgM-, a1-Antitrypsin-, Haptoglobin- und Transferrin-Konzentrationen im Serum von gesunden Erwachsenen

Abstract: Zusammenfassung:Mit Hilfe der Methode der kinetischen Nephelometrie wurde die IgA -, IgG-, IgM-, -Antitrypsin-, Haptoglobin-und Transferrin-Konzentration im Serum von 367 gesunden Blutspendern unter Berücksichtigung des Alters und Geschlechts untersucht. Die gemessenen Parameter zeigten alters-und geschlechtsspezifische Differenzen. Daher wurden die Normalwertbereiche getrennt für alle Gruppen dargestellt. Schlüsselwörter: IgA, lgG f IgM, -Antitrypsin, Haptoglobin, Transferrin -Normwertbereiche -gesunde Erwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
2

Year Published

1982
1982
1985
1985

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 5 publications
1
2
0
2
Order By: Relevance
“…In accordance with other investigators (2,4,7,8) an increase with age was found for IgA and haptoglobin, whereas sex associated differences were seen for IgM, IgG, a r antitrypsin (higher values for women) and IgA, C3, C4, oc r acidglycoprotein (higher values for men), although not in all age groups. As the sex associated differences first of all are based on the exceptional position of subgroup 3 (women aged 19 -39 years), they may be conditioned by the hormonal state of women capable of bearing children.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In accordance with other investigators (2,4,7,8) an increase with age was found for IgA and haptoglobin, whereas sex associated differences were seen for IgM, IgG, a r antitrypsin (higher values for women) and IgA, C3, C4, oc r acidglycoprotein (higher values for men), although not in all age groups. As the sex associated differences first of all are based on the exceptional position of subgroup 3 (women aged 19 -39 years), they may be conditioned by the hormonal state of women capable of bearing children.…”
Section: Discussionsupporting
confidence: 92%
“…The normal distribution tnmcated on the left side at c is defined by the following function If c is known, the estimation of μ and σ in F (x) can made by an iterative algorithm, using χ and s 2 of the sample 0) ( Χί -χ) 2 and repeated calculation of part k, until changes of μίς and a k are sufficiently small k) l -< To find the best estimation c of c, and consequently the corresponding set (c, μ^ d c ), a discrete set of values c < χ,^ was taken to calculate the set (c, μ € , a c ), using the above given estimator for each c. The set (c, μ ϋ , a c ), which gives the best fit in the Kolmogorov-Smirnov test was taken s estimator (c,…”
Section: Appendix Bmentioning
confidence: 99%
See 1 more Smart Citation
“…Beckman Instruments. über die Methodik (11) und die Kontrolle (5,12) der Bestimmungen mit diesem Immunchemie-System wurde bereits an anderer Stelle ausführlich berichtet.…”
unclassified
“…Die Beurteilung des aj-Antitrypsin-Wertes ist dadurch erschwert, daß Abhängigkeiten beschrieben sind: In der Schwangerschaft und bei Einnahme oraler Kontrazeptiva wurden erhöhte Werte gefunden (l, 6, 7). Weniger gesichert scheinen Geschlechts-und Altersabhängigkeiten zu sein (7,8,9).…”
Section: Introductionunclassified